Islam Progresif dan Kesetaraan Gender Menurut Pemikiran Abdullah Saeed - Rusdiana Navlia Khulaisie (MUWAZAH : jurnal kajian gender, 2019)
This paper describes progressive Islam. Progressive Islam is Islam that offers a contextualization of the interpretation of opened, friendly, fresh, and responsive Islam to every humanitarian issue. According to Omid Safi, progressive Islam is a continuation and extension of the liberal Islamic movement that emerged since about one hundred and fifty years ago. On the other hand, this trend is also emerg as an expression of their dissatisfaction to the liberal Islamic movement which emphasized internal criticism of the views and behavior of Muslims who were not or less compatible with humanist values. While the aspects of modernity, colonialism and imperialism did not get enough attention from the Liberal Islamic movement. Abdullah Saeed on this occasion offered the concept of understanding Islam that could answer the needs of the contemporary Moslem society so that it could be applied as ṣālih li kulli zamān wa makānteaching.